Prosodic Patterns in Spoken Academic English: Their Role in Meaning Construction and Discourse Organization - Jimmi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines how prosodic patterns contribute to meaning construction and discourse organization in spoken academic English. Although prosody has been widely recognized as an important feature of spoken communication, its specific role in structuring academic arguments and guiding listener interpretation remains insufficiently explored. Using a qualitative discourse-analytic design supported by descriptive acoustic quantification, this study analysed 15 recordings of spoken academic English collected from one faculty at a university in Indonesia. The corpus consisted of 6 English-medium lectures, 6 academic seminar presentations, and 3 academic discussions, with a total duration of approximately 10 hours and 20 minutes involving 12 academic speakers. The unit of analysis was the academic discourse segment, and 248 segments were identified as having clear prosodic functions. Acoustic analysis using Praat was conducted to examine intonation, pitch movement, stress placement, intensity, pauses, and speech-rate variation. The findings show that rising intonation was mainly used to introduce new topics, claims, and subpoints, while falling intonation marked closure, conclusion, and certainty. Stress placement, increased intensity, pauses, pitch shifts, and speech-rate variation also supported emphasis, transition, argument structuring, and listener guidance. These findings indicate that prosody is not merely a pronunciation feature, but a discourse-level resource that shapes coherence, salience, and academic meaning-making.